Utopian Idea of Political Project in Global South Nowadays: From Anti-Colonial Struggle to Economic Agenda - Yunazwardi, Muhammad Iqbal; Facrurreza, Ahmad Mujadid; Ningsih, Sabda (Global Focus, 2026)
This article examines the shifting meaning of the Global South from its roots in anti-colonial political solidarity that embodied by the Bandung Conference and the Non-Aligned Movement (NAM), toward a predominantly economic agenda characterized by South-South cooperation initiatives like BRICS, NAASP, and G77+. Employing a qualitative method, this study analyzes historical documents, key literature, and institutional texts to trace the transformation of the Global South narrative across different geopolitical contexts. It argues that while these contemporary frameworks invoke the legacy of Bandung and Third Worldism, they largely fail to revive the original political project aimed at resisting neocolonialism and global inequality. Instead, such initiatives often reflect the pragmatic interests of sub-imperial powers like China and Russia, who tend to reproduce exploitative structures reminiscent of the Global North. The Bandung Spirit, once a symbol of decolonial solidarity and transformative political agency, has been reduced to rhetorical symbolism, with economic cooperation now shaped more by neoliberal imperatives than emancipatory goals. The article concludes that the contemporary Global South risks becoming a site of co-optation rather than liberation, lacking a substantive alternative to the dominant neoliberal global order